2020
DOI: 10.1007/s13744-020-00819-1
|View full text |Cite
|
Sign up to set email alerts
|

Midgut Genes Knockdown by Oral dsRNA Administration Produces a Lethal Effect on Cotton Boll Weevil

Abstract: The "cotton boll weevil" (Anthonomus grandis Boheman) is a key pest in America whose larval stage develops within the cotton flower bud. During its development, the larva uses the flower bud as food and as a shelter from predators. This behavior limits the effective control through conventional insecticide applications and biocontrol techniques. Increasing genetic information from insects has allowed the development of new control technologies based on the use of RNA interference (RNAi) to design orally delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In insects, the developmental stage has been found to influence RNAi penetrance, a phenomenon resulting from differences in the response to exogenous RNAi triggers ( Schmitt-Engel et al, 2015 ). In general, younger insect developmental stages have been found to be more receptive, or sensitive, to knockdown, compared to more advanced life stages (instars) ( Guo et al, 2021 ; Salvador et al, 2021 ; Willow and Veromann, 2021 ). The psyllid life cycle consists of five nymphal instar stages, the newly emerged adult, also referred to as a teneral adult, and the mature adult ( Butler and Trumble, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In insects, the developmental stage has been found to influence RNAi penetrance, a phenomenon resulting from differences in the response to exogenous RNAi triggers ( Schmitt-Engel et al, 2015 ). In general, younger insect developmental stages have been found to be more receptive, or sensitive, to knockdown, compared to more advanced life stages (instars) ( Guo et al, 2021 ; Salvador et al, 2021 ; Willow and Veromann, 2021 ). The psyllid life cycle consists of five nymphal instar stages, the newly emerged adult, also referred to as a teneral adult, and the mature adult ( Butler and Trumble, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, as mortality was only monitored after 26 days (dsRNA treatments were administered for 20 days), there remain critical unknowns with regard to timeliness of RNAi-induced mortality. Salvador et al (2021) reported that 14 days of dietary exposure, using artificial diet overlaid with treatment solutions containing 0.2 μg dsRNA/μl, resulted in 40–60% mortality in cotton boll weevil ( Anthonomus grandis ) larvae, and 10–30% mortality in adults, percent mortality depending on target gene in both life stages.…”
Section: Observed Rnai Sensitivities In Coleopteramentioning
confidence: 99%
“…Cytochrome P450s are a large group of xenobiotic enzymes that are induced in the cell to handle various stressors including insecticides [ 49 ]. The boll weevil has 59 CYPs in the genome annotated as xenobiotic metabolism and insecticide resistance [ 36 ], of which 23 are found in the gut [ 50 ]. In a previous study, 28 xenobiotic CYPs were shown to be constitutively upregulated in field-collected larvae and adults compared to pupae [ 36 ].…”
Section: Resultsmentioning
confidence: 99%